The Representation of Ethnic Minorities in the Internet Media during the Considerations of the Law on National Minorities - Ilkevičiūtė, Justinas (Žurnalistikos tyrimai, 2017)
The representation of ethnic minorities in the internet media is an important contributor analyzing how powerful media to public policy is. Therefore it is meaningful to analyze the content of media and to reveal assumptions on how media can affect the Law on National Minorities. Ethnic minorities often feel discriminated so media by negatively portraying them can contribute to the disintegration of the minorities and the development of its exclusion. For this reason, the research of media content has been conducted to analyze the characteristics of representation of ethnic minorities in the Internet news portals Delfi.lt, 15min.lt and Lrytas.lt during the period of 2010–2014. The purpose is to reveal the characteristics of representation of ethnic minorities in the Internet media while the Law on National Minorities was considered and to outline the influence of media assumptions on the public policy. Having analyzed the content of internet media related to this Law using qualitative method, it was concluded that ethnic minorities are portrayed negatively. Ethnic minorities’ content analysis showed that the most negatively portrayed minority is the Polish ethnic minority which is identified with the Lithuanian Poles’ Electoral Action and its policies. The negative image of Polish minority is created by describing it using negative connotation expressions, stating that public policy problems arise from it, creating stereotypes. These characteristics of ethnic minorities’ representation are often submitted in the most prominent news sites. It may create a negative image of them and have an impact on public policy and the Law on National Minorities which has not been passed for five years. By negatively portraying the Polish ethnic minority the media can contribute to the disintegration and the development of its exclusion.
Keywords: ...